Strong plasmon-Wannier Mott exciton interaction with high aspect ratio colloidal quantum wells - Yu, Junhong (2021)
The strong interaction between excitons and plasmons, manifested as Rabi splitting of the eigen energies, is of fundamental interest for manipulating photons in nanoscale devices. Thanks to their enhanced photostability and minimal inhomogeneous broadening compared with organic molecules, inorganic emitters are preferred for practical applications. However, a relatively small Rabi splitting with inorganic materials severely hinders the active plasmonic operation, considering its weak optical nonlinearity and slow energy interexchange. Here, we circumvent this problem in a hybrid system consisting of high aspect ratio colloidal quantum wells (HARCQWs) and an individual plasmonic silver nanocube. By taking advantages of a highly in-plane oriented exciton, enhanced exciton binding energy, and non-stacking properties in HARCQWs, we demonstrate an unprecedented giant Rabi splitting energy up to 400 meV under ambient conditions, which is observed not only in scattering but also in photoluminescent spectra. These findings are a key step toward achieving inorganic plasmonic devices.